Estudo do comportamento e da resistencia das vigas mistas aço-concreto constituídas por perfis formados a frios e lajes pré-fabricadas - Luciano Augusto Figueiredo de Oliveira (2001)
The studies and the results of the theoretical-experimental investigation realized at the Experimental Analysis Laboratory of Structures, of the Structures Department of UFMG School of Engineering, are presented. First are presented the studies of the behavior and resistance of U cold-formed shear connector type, followed by the investigation of a technological innovation, related to hexagonal headed stud connectors, fixed with rivets with thread interns. It is analyzed the behavior and the resistance of composite steel-concrete beams, using cold-formed profiles, precast concrete slab and the shear connectors type listed above, seeking the application in residential 04-story constructive systems.